Factors inflencing the level of adoption in electronic commerce among SMEs - Abdul Aziz, Faieza; Jamali, Negar (Institute of Information System & Research Center, 2013)
Small and medium-sized enterprises (SMEs) contribute heavily to economic growth, social structure and employment as well as regional and local development. Consequently, they have become a significant sector of the economy. The lack of e-commerce (EC) research on SMEs in developing countries is challenging because the findings of previous EC studies on SMEs of developed countries cannot be freely generalized to the context of SMEs of developing countries. To help SMEs, in particular those in developing countries, with EC adoption, this research investigates the factors within the Technological Organizational Environmental (TOE) framework that affect the decision to adopt EC as well as the adoption and non-adoption of different EC tools. Furthermore the current research attempted to investigate the level of EC adoption in SMEs. A questionnaire-based survey using a quantitative approach is conducted. Two hundred thirty five manufacturing SMEs were selected as respondents in this work. The findings showed that seven out of ten factors have significant positive relationships with EC adoption, which were buyer/supplier pressure, support from technology vendors, perceived compatibility, CEO innovativeness, perceived relative advantage, competition and information intensity. Moreover, results showed that 57.02 percent of SMEs adopted EC.